Anisa dan Gothic Feminisme dalam Novel Malam Seribu Jahanam Karya Intan Paramaditha - Mayada Mayada; Agus Sulton (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe discrimination against the character Anisa and gothic feminism in the novel Malam Seribu Jahanam by Intan Paramaditha. The data source in this study is the novel Malam Seribu Jahanam by Intan Paramaditha published in 2023. The data in this study are phrases, words, clauses in the excerpts of the novel Malam Seribu Jahanam. The data collection technique used in this study uses document techniques or library techniques. The data analysis technique used in this study is qualitative data analysis. The data validity technique used by the author in this study is triangulation. The results obtained were that Anisa experienced inequality in the family circle, she often got oppression from her older sister. Her two older sisters often never considered Anisa to be never whole. Anisa's action of taking steps to become a bomb bride as a form of self-proof to the people around her, that she was not weak as her sister had thought all this time.